Digital Literacy of Rural Households in Bangladesh - Shadat, Md. Wasel Bin; Islam, Md. Saiful; Zahan, Iffat; Matin, Maria (BRAC Institute of Governance and Development (BIGD), 2022)
As more public and private sector services are being digitized to make them more accessible to citizens, digital literacy is becoming an increasingly essential skill needed to reap the fullest benefits from these services. Without people possessing the necessary digital skills, the benefits of information and communication technology (ICT)-driven public initiatives will not reach the entire country. The same holds true for Bangladesh, which aspires to become a fully digitized nation. The objective of this research is to (a) explore the current state of digital literacy in rural Bangladesh, (b) investigate the determinants of digital literacy, and (c) develop the first-ever digital literacy index (DLI) for Bangladesh, which we named “DLit_BIGD 1.0”.